La revegetación en las montañas españolas. ¿Dejar hacer o intervenir en el territorio? - Lasanta, Teodoro; Vicente-Serrano, Sergio; Arnáez, José (Geographicalia, 2014)
Natural revegetation is the main effect of the productive marginalization in the Spanish mountains. This process has both positive and negative effects and two alternative scenarios future can be considered:i) to leave the lands to the natural revegetation without human interference and ii) to apply land management practices to control revegetation.This work provides information based on case-studies from the Pyrenees and the Iberian Range about the impact of the clearance of shrub areas, in abandoned fields. Our data show that the replacement of the shrubsby pastures in selected areas has very few negative consequences and several positive impacts: i) the increase of water resources, ii) more forage production, iii) better seasonal balance in the availability of pastures, iv) a more diverse landscape and v) the reduction of the fire risk.